Admission cardiotocography as a screening test in high risk pregnancies and its co-relation with peri-natal outcome - Behuria, Sasmita; Nayak, Rohani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Birth asphyxia which results due to deprivation of oxygen to the foetus during the birth process is still the leading cause of perinatal death. So the labour should be monitored by an effective method. Electronic foetal monitoring is quite promising in this regard. The present study was done to project the effectiveness of cardiotocography (CTG) at admission to labour room in high risk pregnancies as a predictor of perinatal outcome. Methods: This is a randomized prospective study conducted in the labour room of SCB Medical College, over a period of 1 year (April 2013 to April 2014) at Cuttack, Odisha, India. All women randomized for the study were subjected to initial admission CTG in the 1st stage of labour. Those with a normal/reassuring admission test, monitored by intermittent auscultation method and those with abnormal test were monitored by continuous CTG. Foetal and perinatal outcome were co-related with admission CTG. Results: Foetal distress during labour developed in 29 % of patients with a normal test and in 64% of patients with an abnormal test. The admission test had a sensitivity of 44% specificity 95% of and a positive predictive value of 50% for predicting an APGAR score 5 min after birth. Neonatal admission to SNCU was required in 29% of patients with a normal test and 45% of patients with an abnormal test. Conclusions: Labour admission CTG should be used for screening but not a sole diagnostic test of compromised foetus. It is found to be valuable in high risk pregnancy.